Navodila za izdelavo pisnih del na Ekonomsko-poslovni fakulteti Univerze v Mariboru - Sternad Zabukovšek, Simona; Boršič, Darja; Tominc, Polona; Štrukelj, Tjaša (2020)
Instructions for Written Works at Faculty of Economics and Business, University of Maribor. During the course of their studies, each student encounters the creation of written works. The first step is the seminar work within individual courses, intended precisely for us to learn to research, to search for sources of data and other information, to express ourselves professionally, to form our thoughts and to appropriately shape the final appearance of the text. This knowledge is then shown in the final works at the end of the study, where the content and format of such written work is especially important. The manual is constructed in such a way that the chapters follow in the same way as in any written work, except for the colophon and the preface, which are not otherwise necessary in the written works. Each chapter explains the essential features of the chapter. Below the "attention" tag are the most common mistakes we should pay particular attention to and avoid. The example label shows the layout of the individual elements. Also, command hints in Microsoft Word 2019 have been added for easier work.
Keywords: typology of written works; compulsory components of written work; reference to literature and sources; form of written work